Autonomic Innervation from the Aortic Root Ventricular Ganglionated Plexi to the Pulmonary Vein: A Novel Pathway - Hong-Tao Wang; Bo-Yuan Fan; Fei-Fei Su; Di Zeng; Tao Chen; Qiang-sun Zheng (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2015)
Background: Autonomic nerve innervation pathway from the ventricular GP to the pulmonary veins (PV) remains unclear. Aim: This study investigates the autonomic innervations from aortic root ventricular GP to the PVs. Nissl's staining and fluorescent dual label staining were performed to determine the neuron structure in the aortic root GP in five dogs. Avidin Biotin Complex (ABC) staining were performed to study the efferent autonomic pathway from the aortic root GP to the PVs. Results: Adrenergic and cholinergic neurons were both present in the aortic root GP, with the majorities were cholinergic. ABC positive nerve fibers that contained both cholinergic and adrenergic neurotransmitters penetrated directly from the aortic root GP to the left PVs. Conclusion: Autonomic innervation of the Left PVs is partly originated from the aortic root ventricular GP.